The multimodal performance of conversational humor - Gironzetti, Elisa (Figurative thought and language ;, 2022)
"This volume is the first monograph exploring the functions of visual cues in humor, advocating for the development of a non-linguocentric theory of humor performance. It analyzes a corpus of dyadic, face-to-face interactions in Spanish and English to study the relationship between humor, smiling, and gaze, and shows how, by focusing on these elements, it is possible to shed light on the "unsaid" of conversations. In the book, the humorous framing of an utterance is shown to be negotiated and co-constructed dialogically and multimodally, through changes and patterns of smiling synchronicity, smiling intensity, and eye movements. The study also analyzes the multimodal features of failed humor and proposes a new categorization from a dialogic perspective. Because of its interdisciplinary approach, which includes facial expression analysis and eye tracking, this book is relevant to humor researchers as well as scholars in social and behavioral sciences interested in multimodality and embodied cognition"--